‘In this job, you cannot have time for family’: work–family conflict among prison officers in Ghana - Akoensi, Thomas D. (Criminology & criminal justice, 2018)
This article documents the experience of work-family conflict (WFC) among prison officers in Ghana. Although the term WFC has been used in relation to prison officers in the UK and the USA, the context of WFC in Ghana is unusual. In this predominantly collectivist culture, family responsibilities include obligations to the extended family. WFC is mainly unidirectional, with interference running from work to the family. Officers are thus impaired in fulfilling their family responsibilities, which consequently impairs their daily work and mental well-being. The ‘crisis controlling’ or ‘paramilitary’ organizational structure of the Ghana Prisons Service (GPS) makes it very difficult for the work domain of prison officers to accommodate family responsibilities. Female officers appear to bear a heavier WFC burden than male officers, mainly on account of their traditionally unpaid housekeeping role in addition to their paid employment in a masculine organizational culture. The findings are significant, as they show that the promulgation of family-friendly policies to alleviate WFC-associated stress lies in the hands of the GPS, since WFC emanates solely from the work domain.